RAMAN SPECTROMETRY, USED IN THE STUDY OF ZINC OXIDE THIN FILMS - Nicoleta-Maria MIHUT; Aurora Catalina IANASI (Fiabilitate şi Durabilitate)
Starting from the information in the specialized literature that demonstrates the antibacterial effect of zinc oxide nanopowder [9], the aim of the work was to create and characterize thin films of pure zinc oxide but also doped with different concentrations of cobalt, made up of three respectively five depositions and thermally treated at 500°C or 600°C, respectively, on a metallic titanium substrate, using the RA spectrometry technique.